A new idea to improve the cyclic performance of end plate beam–column connections. (15th February 2022) - Shaheen, Mohamed A.
Abstract: This paper presents a new idea to improve ductility and energy dissipation of seismic beam–column end plate connections by improving the contribution of the bolts to the rotation capacity. The load path in the connection is interrupted by inserting a steel sleeve, with a designated wall curvature, between the washer and the end plate, promoting a more ductile response, particularly when the sleeve is the weakest element in the load path. An analytical solution is firstly proposed to define the sleeve parameters that satisfy the sleeve fails before the failure of any other connection components. Subsequently, the cyclic performance of the end plate connection with various sleeve parameters is investigated through validated FE models. Results showed that the ductility and energy dissipation of the proposed sleeved connection are 2.86 and 3.88 times that of the standard configuration, respectively. Furthermore, the elastic response is consistent with the standard configuration indicating that the proposed sleeve system is compatible with existing codified elastic design approaches without modification. Graphical abstract: Highlights: The idea comprising a steel sleeve inserted between the washer and the endplate. An analytical equation is presented for the proposed system. The energy dissipation of the new system is 3.9 times that of standard connection. The ductility of the new system is 2.9 times that of standard connection. The load-bearing capacity of the new system is 1.1 times that of standard connection.